2019
DOI: 10.2196/10664
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone–Based Telemedicine Practice in Older Chinese Patients with Type 2 Diabetes Mellitus: Randomized Controlled Trial

Abstract: Background Previous studies on telemedicine interventions have shown that older diabetic patients experience difficulty in using computers, which is a barrier to remote communication between medical teams and older diabetic patients. However, older people in China tend to find it easy to use mobile phones and personal messaging apps that have a user-friendly interface. Therefore, we designed a mobile health (mHealth) system for older people with diabetes that is based on mobile phones, has a strea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(114 citation statements)
references
References 30 publications
(36 reference statements)
1
111
0
2
Order By: Relevance
“…The duration of mobile app interventions varied from 3 to 12 months. Most studies were conducted in American or European countries and only five in Asian countries .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The duration of mobile app interventions varied from 3 to 12 months. Most studies were conducted in American or European countries and only five in Asian countries .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 1,741 unique relevant studies retrieved, a total of 14 RCTs were included in this meta-analysis upon the exclusion of 1,727 studies with the reasons listed in Figure 1 (9)(10)(11)(12)(13)(14)(15)(16)(17)(24)(25)(26)(27)(28). Specifically, one study was excluded because it was an ad interim report (29), and another was excluded because of inconsistent results on BW and BMI (30).…”
Section: Main Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an mHealth system with advice regarding behavioral and motivational messages, a tracking health app, a Bluetooth device (eg. glucometer) and a web-platform can improve the management and education in their own home [19,26,33,35,43]. The benefits of digital intervention can reduce the frequency of failed contact with patients, and they also have the potential to enhance work practice patterns and health service delivery for clinicians and patients in diabetes management [4].…”
Section: Uc Vs Mhealth Interventionmentioning
confidence: 99%
“…The COVID-19 outbreak also shaped the landscape of follow-ups and shifted it somehow toward telemedicine. In recent years, with the rapid development of modern communication technologies, telemedicine started to gain popularity among medical specialties [11][12][13]. Our patients were not intensive telemedicine users; however, our study indicated the necessity of promoting telemedicine, especially for patients who needed frequent monitoring and medicine adjustments.…”
Section: Discussionmentioning
confidence: 71%